2014
DOI: 10.1002/2013ja019558
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric field‐aligned currents: Simulation results

Abstract: We present simulation results of the 3-D magnetosphere-ionosphere current system including the Region 1 and Region 2 field-aligned currents, ionospheric currents, and interhemispheric field-aligned currents flowing between the northern and southern conjugate ionospheres in the case of asymmetry in ionospheric conductivities in two hemispheres. The model shows that the interhemispheric currents can be an important part of the global 3-D current system in high-latitude ionosphere, especially during summer-winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
(115 reference statements)
1
13
0
Order By: Relevance
“…In previous papers [ Lyatskaya et al ., , ], we showed that during summer/winter conditions, in addition to R1 and R2 currents, also significant IHCs could appear. These IHCs emerge at the gradients of ionospheric conductivity in any hemisphere; it is going along the magnetic field lines between conjugate regions in two hemispheres.…”
Section: Discussion and Main Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In previous papers [ Lyatskaya et al ., , ], we showed that during summer/winter conditions, in addition to R1 and R2 currents, also significant IHCs could appear. These IHCs emerge at the gradients of ionospheric conductivity in any hemisphere; it is going along the magnetic field lines between conjugate regions in two hemispheres.…”
Section: Discussion and Main Resultsmentioning
confidence: 71%
“…Although inside the summer polar cap, the EICs are usually directed to noon; in winter polar cap they decrease in magnitude and turn toward dawn. The reversal in the direction of the EICs at the nightside, which is well seen in both ionospheres, is observed not just at the polar cap boundary (where the R1 currents are located) but equatorward of it in the region of IHCs location; this shows the important role played by the IHCs in nightside winter ionosphere, where the IHCs are, in fact, the main source of ionospheric currents [see also Lyatskaya et al, 2014aLyatskaya et al, , 2014b. A similar equatorward displacement of the convection reversal relatively to the polar cap boundary was earlier reported by Sotirelis et al [2005].…”
Section: 1002/2015ja021167mentioning
confidence: 95%
See 3 more Smart Citations